Integrative Phylogeography Reveals Conservation Priorities for the Giant Anteater Myrmecophaga tridactyla in Brazil - Raphael T. F. Coimbra; Rafael F. Magalhães; Priscila Lemes; Flávia R. Miranda; Fabrício R. Santos (Diversity, 2022)
The giant anteater (Myrmecophaga tridactyla) is a strictly myrmecophagous xenarthran species that ranges from Honduras to northern Argentina, occupying various habitats, from grassland and floodplains to forests. According to the IUCN, it is a vulnerable species mainly threatened by poaching, habitat loss and fragmentation, and road kills. Here, we investigate the phylogeography, distribution, ecology, and historical demography of Brazilian populations of the giant anteater. We analysed two mitochondrial (mtDNA) and three nuclear (nDNA) markers in 106 individuals from the Cerrado, Pantanal, Atlantic Forest, and Amazon Forest biomes through analyses of population structure and demography, phylogeography, and ecological niche modelling. Two divergent mtDNA clusters were found, one in the Amazon (AM) and another in the Cerrado, Pantanal, and Atlantic Forest biomes (CEPTAF). At the population level, CEPTAF presented higher mtDNA haplotype richness than AM and a unidirectional mtDNA gene flow was identified from AM to CEPTAF, which could be linked to more favourable habitat conditions for the species in Cerrado and Pantanal. Paleodemographic reconstructions with mtDNA and nDNA data indicate a large population expansion of the species starting at the end of the Pleistocene. Finally, the integrative phylogeographic analyses of giant anteater populations reinforce the importance of the Brazilian Cerrado as a priority biome for the species’ conservation.